Pengaruh Media Microsoft Powerpoint Terhadap Hasil Belajar Pendidikan Agama Kristen Kelas VIII SMP Negeri 1 Sianjurmula-mula Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Lidya Irmayani Manurung; Risden Anakampun; Taripar Aripin Samosir; Andar G. Pasaribu; Johari Manik (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
The aim of this research is to find out that the learning outcomes of students taught with Microsoft Power Point media are higher than the learning outcomes of students taught without Microsoft Power Point Media for class VIII SMP Negeri 1 Sianjur for the 2023/2024 academic year. The research hypothesis is: